Efektywność systemów zarządzania działalnością firm użyteczności publicznej na przykładzie komunikacji miejskiej - Zagożdżon, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents problems of efficiency in management of public utility activities. Empirical research area is public transport. Proper analysis of efficiency of different local transportation management systems was preceded by synthetic characteristics of management systems used in economic practice as well as organizational and legal forms of carrier functioning. The analysis of management efficiency was focused on cost efficiency of testing solutions as well as on the influence on the efficiency by public transport markets competition and opening the market to private carriers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 690-699